Apigenin attenuates depressive-like behavior via modulating monoamine oxidase A enzyme activity in chronically stressed mice - Juliet N. Olayinka; Oluwole B. Akawa; Emmanuela K. Ogbu; Anthony T. Eduviere; Raymond I. Ozolua; Mahmoud Soliman (Elsevier, 2023)
Chronic stress is a risk factor for depression and is characterized by elevated levels of brain monoamine oxidase A (MAOA). Mounting evidence has shown that MAOA is a biochemical link between stress and depression. Apigenin (API), a natural flavonoid, as demonstrated in vitro inhibitory effect on MAOA, is suggestive of antidepressant-like activity. However, the in vivo inhibitory effect of API on MAOA and how it affects depression still remain unclear. Here, we report the probable mechanisms of action of API in chronic unpredictable mild stress (CUMS)-induced depression in mice. Treatment with API reversed anhedonia, and reduced anxiety and immobility time in behavioral studies. API reduced brain corticosterone and malondialdehyde (MDA) levels but increased brain levels of glutathione and superoxide dismutase. Furthermore, interleukin-6 and tumor necrosis factor-α were attenuated by API. It also restored cell loss and inhibited the activity of MAOA in the hippocampal brain regions and prefrontal cortex. Comparative binding affinity of API for MAOA (-7.7 kcal/mol) through molecular docking studies was greater than that of reference compound, clorgyline (-6.8 kcal/mol). Favorable hydrophobic interactions important to API binding at MAOA binding cavity was revealed to include conventional hydrogen bond (Cys323 and Tyr444), π-Sulfur (Cys323), π-π Stacked (Tyr407), π-π T-shaped (Phe208), π-lone pair and π-alkyl (Ile335, Ile180) interactions. These results suggest that API is a potent, selective, reversible inhibitor of MAOA with capability of attenuating CUMS-induced depression via inhibiting MAOA enzyme activity and altering other pathomechanisms.